An 18-year review of sports groin injuries in the elite hockey player: clinical presentation, new diagnostic imaging, treatment, and results - Brown, R. A.; Mascia, A.; Kinnear, D. G.; Lacroix, V.; Feldman, L.; Mulder, D. S. (Clinical Journal of Sport Medicine, 2008)
Objective: This is a retrospective study of 98 hockey players who underwent 107 surgical explorations for refractory lower abdominal and groin pain that prevented them from playing hockey at an elite level. Design: Retrospective chart review combined with a complete follow-up examination and questionnaire. Setting: The players were treated in an ambulatory care university tertiary care centre. Patients: A total of 98 elite hockey players underwent 107 surgical groin explorations for intractable groin pain preventing their play. Follow-up was 100%. Intervention: Each player had repair of a tear of the external oblique muscle and fascia reinforced by a Goretex mesh. The ilioinguinal nerve was resected in each patient. Outcome Measures: There was absence of groin pain on the return to play hockey at an elite level. Results: In all, 97 of 98 players returned to play after the surgical procedures. No morbidity was attributed to division of the ilioinguinal nerve. Conclusions: Surgical exploration of the involved groin with repair of the torn external oblique muscle and division of the ilioinguinal nerve has resulted in resolution of refractory groin pain and return to play in the elite hockey player. The surgical procedure is associated with a low morbidity. Recent observations on dynamic ultrasound show promise in accurately diagnosing this injury.